Case Report Diagnosis and Management of Essential Trombositosis in RSUD Sanjiwani Gianyar and RSUP Sanglah - Ni Wayan Sri Wardani; I Ketut Ery Purnama Warsana Putra; Ni Made Renny A Rena (WMJ (Warmadewa Medical Journal), 2018)
Abstract. Essential thrombocythemia (ET) is a very rare disorder with 1- /100,000 population in the world. The incidence of this abnormality is still obscure in Indonesia. We report a case of ET, women of age 74 years old that came to Sanjiwani Hospital with gum bleeding. This case is confirmed based on WHO criteria of ET which are the increasing of thrombocyte of a number of increase >450 /ÂµL3, proliferation of megakaryocyte cell on bone marrow biopsy, also not meeting any other WHO criteria for also not meeting any other WHO criteria for BCR-ABL1+CML, Polycythemia Vera, Chronic Myeloid Leukemia, Myelodysplastic Syndrome, or other myeloid neoplasm diseases. Management of this case is based on risk adapted treatment algorithm considering three major risk factors for thrombosis (history of thrombosis, JAK2/MPL mutations, and advanced age). This case is categorized as high risk patient for thrombosis, so that treated with antiplatelet aggregation (aspilets) and anagrelide after hydroxyurea clinically unresponsive.